Multi-agent model based on combination of chemical reaction optimisation metaheuristic with Tabu search for flexible job shop scheduling problem. (2018) - Marzouki, Bilel; Driss, Olfa Belkahla; Ghédira, Khaled
Scheduling in production systems consists in assigning operations on a set of available resources in order to achieve defined objectives. The flexible job shop scheduling problem (FJSP) is one of the scheduling problems and also an extension of classical job shop scheduling problem such that each operation can be processed on different machine and its processing time depends on the used machine. This paper proposes a multi-agent model based on combination of chemical reaction optimisation metaheuristic with Tabu search to solve the FJSP in order to minimise the maximum completion time (makespan). To evaluate the performance of our model, experiments are performed on well known benchmark instances proposed in the literature and comparisons are made with other approaches in literature.